1992
DOI: 10.1007/bf01738432
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the constitutively active proteolytic fragment of protein kinase C on the contractile properties of demembranated smooth muscle fibres

Abstract: The role of protein kinase C (PKC) in regulating the contractile state of smooth muscle was investigated using the constitutively active catalytic fragment of PKC (PKM) with skinned (demembranated) chicken gizzard fibres. PKM attenuated a submaximal contraction in gizzard smooth muscle skinned fibres, but not in rabbit cardiac skinned fibres. PKM-mediated relaxation of submaximal contractions of smooth muscle was accompanied by a reduction in the rate of ATP hydrolysis in the fibre and by phosphorylation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 60 publications
3
11
0
Order By: Relevance
“…Furthermore, PKM treatment of skinned fibers submaximally contracted at pCa 5.6 induced relaxation. On the other hand, maximal contractions occurring at pCa 3.8 were unaffected by PKM addition or pretreatment (Parente et al 1990(Parente et al , 1991. These results, which are consistent with the conclusions of other skinned fiber studies (Inagaki et al 1987) and the in vitro effect of PKC phosphorylation of myosin that reduces the actin-activated M~~+ ATPase activity (Nishikawa et al 1983), indicate that, at least at submaximal [ca2+], PKC-catalyzed phosphorylation of myosin can affect contraction.…”
Section: Protein Kinase Csupporting
confidence: 91%
“…Furthermore, PKM treatment of skinned fibers submaximally contracted at pCa 5.6 induced relaxation. On the other hand, maximal contractions occurring at pCa 3.8 were unaffected by PKM addition or pretreatment (Parente et al 1990(Parente et al , 1991. These results, which are consistent with the conclusions of other skinned fiber studies (Inagaki et al 1987) and the in vitro effect of PKC phosphorylation of myosin that reduces the actin-activated M~~+ ATPase activity (Nishikawa et al 1983), indicate that, at least at submaximal [ca2+], PKC-catalyzed phosphorylation of myosin can affect contraction.…”
Section: Protein Kinase Csupporting
confidence: 91%
“…Several reports have shown that direct application of PKC enzyme in heavily permeabilized smooth muscles, which still retained the regulatory/contractile apparatus including MLC kinase and phosphatase, failed to cause an increase in contractile force levels at submaximal levels of Ca 2+ (Inagaki et al 1987; Sutton & Haeberle, 1990; Parente et al 1992). This is in contrast to the Ca 2+ ‐sensitizing effect of PKC activators in intact and mildly (α‐toxin‐ or β‐escin‐) permeabilized smooth muscles (Masuo et al 1994).…”
mentioning
confidence: 99%
“…Sev eral investigators have suggested that PKC-catalyzed MLC phosphorylation is not involved in the regulation of smooth muscle contraction [11][12][13], In fact, if phosphory lation at the PKC sites plays any role in crossbridge regu lation it is to inhibit activity [35,36], In addition, phos phorylation of the MLC kinase during phorbol esterinduced contractions of intact tissue does not appear to be of physiological importance [37], As such, the MLC kinase/phosphatase system and the thick filament do not appear to be responsible.…”
mentioning
confidence: 99%